Analisis Dan Evaluasi Proses Bisnis Layanan Pendaftaran Penduduk Menggunakan Teknik Eliminate, Simplify, Integrate And Automate (ESIA) (Studi Kasus: Dinas Kependudukan dan Pencatatan Sipil Kabupaten Bekasi) - Ilma Bunga Sahara; Buce Trias Hanggara; Nanang Yudi Setiawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The Bekasi Regency Population and Civil Registration Service is a regional government organizer that focuses on public services, one of them is the Population Registration Service. The observation and interview stage conducted by the author of the current business processes at the Population Registration Service resulted in problems such as booming queues that affected the applicant's waiting time, as well as the number of miscommunications and errors in the data listed on the Family Card and Certificate. Therefore, the Population Registration Service Sector calls for an evaluation of the current business processes at the Population Registration Service of the Bekasi Regency Population and Civil Registration Service. The current business process modeling stage uses Business Process Modeling and Notation, then utilizes Failure Mode and Effect Analysis to determine priority improvements which show that filling out the application form has the highest RPN, which is 392, analysis phase used Value Added Analysis and ESIA Techniques in conducting business process evaluation resulted in recommendations for Simplify improvement techniques for filling in submission forms and recording data into the population database, as well as recommendations for Eliminate's improvement techniques for file submission activities and submission of files to data recording officers.